2017
DOI: 10.3390/met7100410
|View full text |Cite
|
Sign up to set email alerts
|

Magnetostriction of Ni2Mn1−xCrxGa Heusler Alloys

Abstract: Among the functionalities of magnetic Heusler alloys, magnetostriction is attracting considerable attention. The alloy Ni 2 MnGa has a premartensite phase, which is a precursor state to the martensitic transition. Some researchers have observed magnetostriction in this alloy in the premartensite phase. We performed magnetostriction studies on the premartensite phase of related Cr-substituted Ni 2 Mn 1−x Cr x Ga alloys and measured the thermal strain, permeability, magnetisation, and magnetostriction of polycry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 46 publications
2
17
0
Order By: Relevance
“…The value of T C for x = 0.00 (Ni 2 MnGa) has been found to be 375 K, using the same approach [16]. For 0x0.25, the premartensitic phase was observed before the martensitic transition occurred [27,28,29]. Singh et al performed X-ray measurements and demonstrated that the crystal structure of Ni 2 MnGa in the premartensitic phase was a 3M-like incommensurate structure [30].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The value of T C for x = 0.00 (Ni 2 MnGa) has been found to be 375 K, using the same approach [16]. For 0x0.25, the premartensitic phase was observed before the martensitic transition occurred [27,28,29]. Singh et al performed X-ray measurements and demonstrated that the crystal structure of Ni 2 MnGa in the premartensitic phase was a 3M-like incommensurate structure [30].…”
Section: Resultsmentioning
confidence: 99%
“…The reaction products were encapsulated in evacuated silica tubes and heated at 1073 K for 3 days and 773 K for 2 more days, then quenched in water. A detailed explanation of the experimental procedure has been given in a previous studies [16,27].…”
Section: Methodsmentioning
confidence: 99%
“…This first order magnetostructural transition (FOMST) involves significant changes in the thermal, magnetic, elastic and transport properties. Apart from the MCE, they are also known to show giant magnetoresistance (MR) [4][5][6][7], magneto-thermal conductivity [8], magnetostriction [9,10], etc. Most of these multifunctionalities are connected with the change in structural and magnetic properties across the FOMST.…”
Section: Introductionmentioning
confidence: 99%
“…Ferromagnetic alloys, which exhibit the shape memory effect (Heusler alloys), belong to the class of functional (smart) materials [1][2][3][4][5][6][7][8][9][10]. The configuration of structures made of such materials can significantly change under the action of external thermal, magnetic, or electric fields.…”
Section: Introductionmentioning
confidence: 99%